The State of Hypertension Guidelines: 2012 - Vinall, Maria (MD Conference Express, 2012)
For most clinicians, one of the most anticipated guideline updates is the Eighth Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 8). The JNC 8 has been in development for some time and is expected to be released by the end of 2012. This article provids an update on the process and timing for these eagerly awaited guidelines.